Local recurrence after radical nephrectomy for kidney cancer: management and prediction of outcomes. a multi‐institutional study. Issue 2 (30th October 2013) - Paparel, Philippe; Bigot, Pierre; Matillon, Xavier; Bensalah, Karim; Salomon, Laurent; Baumert, Hervé; Bastide, Cyril; Thuret, Rodolphe; Karsenty, Gilles; Long, Jean Alexandre; Ammi, Myriam; Bessede, Thomas; et al.
Abstract Background Local recurrence (LR) after radical nephrectomy (RN) for kidney cancer is uncommon. Our objectives were to analyse characteristics and therapeutic options of LR after RN and to identify survival prognostic factors. Materials and Methods From a multi‐institutional retrospective database, we identified 72 patients who experienced LR after RN. Results Mean time to LR was 26.5 ± 3.3 months. The location of the recurrence was renal fossa, regional lymph node, homolateral adrenal and both renal fossa and regional lymph node for 43 (59.7%), 27 (37.5%), 9 (12.5%) and 7 (9.7%) patients, respectively. Patients were treated by surgery, systemic therapies, combination of therapies and palliative treatment in 24 (33.3%), 18 (25%), 24 (33.3%) and 6 (8.4%) cases, respectively. Within a mean follow‐up of 26.4 ± 3.3 months from the date of local recurrence, 12 (16.6%) patients were alive without disease, 30 (41.7%) patients were alive with disease, 30 patients (41.6%) died including 28 (38.8%) from the disease. In multivariate analysis, time to recurrence <1 year (P < 0.001; HR: 4.81) and surgical treatment (P = 0.027; HR: 0.33) were predictive factors. Conclusions Local recurrence after radical nephrectomy is associated with poor prognosis. The time to recurrence and the completeness of the surgical treatment are major prognostic factors. J. Surg. Oncol. 2014 109:126–131. © 2013 Wiley Periodicals, Inc.